2002
DOI: 10.1046/j.1365-2141.2002.03644.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the thrombomodulin gene are rare in patients with severe thrombophilia

Abstract: Summary. Because thrombomodulin plays a key role in the protein C pathway, we evaluated the contribution of thrombomodulin gene mutations to venous thrombosis. We examined 38 patients with recurrent, documented thrombotic events at a young age and a positive family history. Twelve individuals with low levels of soluble thrombomodulin in plasma were also studied. Finally, the allelic frequency of the Ala455Val polymorphism was estimated in 192 patients with at least one thrombotic event and in 369 age-and sex-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The frequency of allele 1418 T in the THBD gene in the current study was 27.7% in all 193 individuals (27.4% in patients and 28.0% in controls), which corresponded to a previous report [8]. Consistent with previous studies [9,10], there was no statistical significant difference in this allelic variant between DVT patients and controls, which suggests that THBD c.1418C N T might be Recently, a large study assessing the genetic background of Chinese venous thrombosis patients [11] confirmed that the c.1456G N T and c.1418C N T variants had no obvious influence on the occurrence of DVT. A large sample study even suggested that the 1418 T allele might increase the stability of thrombomodulin, which would result in an increased protein C activation rate and a lower risk of venous thrombosis [12].…”
Section: Discussionsupporting
confidence: 94%
“…The frequency of allele 1418 T in the THBD gene in the current study was 27.7% in all 193 individuals (27.4% in patients and 28.0% in controls), which corresponded to a previous report [8]. Consistent with previous studies [9,10], there was no statistical significant difference in this allelic variant between DVT patients and controls, which suggests that THBD c.1418C N T might be Recently, a large study assessing the genetic background of Chinese venous thrombosis patients [11] confirmed that the c.1456G N T and c.1418C N T variants had no obvious influence on the occurrence of DVT. A large sample study even suggested that the 1418 T allele might increase the stability of thrombomodulin, which would result in an increased protein C activation rate and a lower risk of venous thrombosis [12].…”
Section: Discussionsupporting
confidence: 94%
“…We also found that the resultant thrombomodulin variants did not protect cultured cells against complement activation. SNPs in the coding region of the THBD gene are rare, 3840 and only eight missense changes are reported in the dbSNP database (www.ncbi.nlm.nih.gov/projects/SNP). One insertion frameshift mutation has been described in a kindred with myocardial infarction, 41 whereas no homozygous mutations have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…DNA sequence analysis revealed a 1456G/T substitution, which results in an Asp468Tyr change. Another study suggested that mutations that affect the function of thrombomodulin (1418C/T) are rarely in association with VTE and low sTM levels, as these levels are affected by a number of variables apart from gene integrity [109]. Another study suggested that mutations that affect the function of thrombomodulin (1418C/T) are rarely in association with VTE and low sTM levels, as these levels are affected by a number of variables apart from gene integrity [109].…”
Section: Polymorphisms/mutations In the Thrombomodulin Gene And Venoumentioning
confidence: 99%
“…This mutant was recently expressed in Cos cells and no impairment of thrombomodulin expression and function could be demonstrated [108]. It appears that mutations that affect the function of thrombomodulin are rarely associated with VTE (Table 1) [ [103][104][105]109]. It appears that mutations that affect the function of thrombomodulin are rarely associated with VTE (Table 1) [ [103][104][105]109].…”
Section: Polymorphisms/mutations In the Thrombomodulin Gene And Venoumentioning
confidence: 99%